What are the public health implications of the life course perspective?. Issue 1 (1st January 2019) - Aagaard-Hansen, Jens; Norris, Shane A.; Maindal, Helle Terkildsen; Hanson, Mark; Fall, Caroline
ABSTRACT: During the past decades innovative research has shown that exposure to harmful events during pregnancy and early infancy ('the first 1000 days') has an impact on health at subsequent stages of the life course and even across generations. Recently it has been shown that even the pre-conception period is of outmost importance, and other scholars have made the case that the 1000 days should be extended to a period of 8000 days post-conception. The present contribution aims to bridge further the gap between research evidence and public health policy by applying a holistic 'full-cycle' perspective. Thus, a conceptual framework is suggested for guiding public health prioritization, including the variables of 'impact on the next generation', 'plasticity' and 'available interventions with documented impact'. This framework could guide decision makers in selecting at which stages of the life course to invest (and not), and furthermore it points to some pertinent research priorities.